Birth beyond borders: childbirth experiences of migrant women in Cape Town, South Africa - Semenya, Mmapitsi (Department of Public Health and Family Medicine, 2026)
Background Childbirth is significant for women and how it unfolds can influence the outcome of labour and have lasting impacts on them. It is important for women to receive good quality care during this time of intense vulnerability. However, evidence suggests that women are at risk of disrespect and abuse during this phase. South Africa is a top destination for migrants from Africa and migrant women may be more likely to experience discrimination during childbirth. This study therefore aims to explore the childbirth experiences of migrant women and will contribute to our understanding of how to address their health care needs during childbirth. Methods The qualitative study was conducted in Cape Town, South Africa. Using an exploratory approach, participants were purposively sampled in collaboration with the Scalabrini Centre of Cape Town. The study included eight women from various African countries. Participants were interviewed using a semi-structured interview guide and thematic analysis was applied to the data. The reproductive justice framework was used to organise interview findings. Results The study revealed that migrant women had positive experiences during childbirth but also reported negative events. Women were satisfied with health care services in South Africa, compared to their countries of origin. Particularly that they didn't have to pay for services, health care workers (HCW) provided them with information about health care procedures and HCW were available to assist them when they needed help. Some women however, reported being neglected, treated unfairly and discriminated against. Some, especially negative experience, might have not been exclusive to migrant women but might have been worsened because of their migration status. Conclusion Women reported having positive childbirth experiences. However, the study also revealed that even though South African legislations protect migrant's right to health, migrant women still experience negative experiences during childbirth. Some negative experiences may have been heightened because of discrimination against migrants in public health care facilities. Therefore, it is essential that interventions are developed, such as the use of interpreters, to support migrant women during childbirth. Furthermore, healthcare workers must adhere to the already existing legislation, and migrant women must be provided with information on accessible channels to report any ill-treatment during childbirth.